Susceptibility of ten red clover (Trifolium pratense) cultivars to six viruses after artificial inoculation - Jana Fránová; Hana Jakešová (Plant Protection Science, 2014)
Seedlings of Trifolium pratense L. cultivars were mechanically inoculated with Czech isolates of Alfalfa mosaic virus (AMV), Clover yellow mosaic virus (ClYMV), Clover yellow vein virus (ClYVV), Red clover mottle virus (RCMV), White clover mosaic virus (WClMV), and a newly discovered member of the Cytorhabdovirus genus. WClMV infected 75.4% of clover seedlings; cv. Rezista was the most susceptible (93.3%), while cv. Fresko was the least susceptible (58.3%). RCMV infected 59.6% of plants; the most susceptible was cv. Tempus (77.6%), the least susceptible cv. Sprint (38.3%). While WClMV infected a higher number of seedlings, RCMV revealed more severe symptoms on affected plants. On the basis of ELISA and RT-PCR results, no cultivar was susceptible to mechanical inoculation with ClYMV and cytorhabdovirus. Moreover, cvs Fresko and Sprint were not susceptible to ClYVV and AMV, respectively.